Assessing the user experience of airlines websites in Malaysia based on customer centered design - Syahrul Nizam, Junaini; Yee, Andy Wee (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The explosion of the World Wide Web has significantly transformed the airline industry. Hence the online ticketing has become a famous and convenient way. As a result, the demand towards this system has tremendously increased. This system supports to reduce the service cost hence presents the possibility to offer cheaper fare. Consequently, the customer is offered with vast range of airlines web sites. Obviously they prefer a site that is more usable. The fundamental problem that motivates this study is to find the factors that determine customer acceptance of the airlines web site. Through the experimental study, the features of three airlines web sites in Malaysia, which are AirAsia (www.airasia.com), Malaysia Airlines (www.mas.com.my) and StarAir (www.starair-online.com) have been analyzed. We present a theoretical framework that highlights the importance of (1) convenient booking flow; (2) efficiency; (3) ease of use; (4) interactivity; and (5) attractiveness; to attract the customers. The result of this research provides a basis for better user experience assessment of the airlines web sites. We end with suggestions for better airlines web site usability based on customer centered design.